Clinical Characteristics and Management of Adolescent Ovarian Cysts - Retnowati, Sulistiari; Wahyuni, Alfaina; Tritia Widiantara, I Nyoman; Nisrina, Hana (Indonesian Journal of Obstetrics and Gynecology, 2025)
Objective : The aim of this study to give clinical characteristic of ovarian cysts in adolescent patient and comprehend the delineation of the management protocol implemented in patients diagnosed with ovarian cysts Methods : This study used a retrospective method conducted by reviewing patient medical records. This study was conducted by collecting medical record data retrospectively for 5 years at PKU Muhammadiyah Gamping Hospital and Panembahan Senopati Bantul Hospital. All data of outpatients, and inpatients diagnosed with ovarian cysts from January 2018 to July 2023 aged 11-21 years were taken to be included in the study. Results: A total of 56 adolescent patients were identified with ovarian cysts. Researchers found most patients with adolescent age group 18-21 years (n=43). Patients presented with a chief complaint of abdominal pain and the cyst was unilateral. Conclusion :. The patients exhibited a primary concern of pain, and the cyst was found to be located on one side only. Efforts to save the ovary were deemed vital owing to the relatively low probability of cyst malignancy. In this study also found that there were no correlation between clinical symtopms (abdoment pain, nausea and menstrual disorder) with size of cyst. Keywords: adolescents, clinical characteristic, ovarian cyst, management